2007
DOI: 10.1001/jama.297.22.2502
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Resynchronization Therapy for Patients With Left Ventricular Systolic Dysfunction

Finlay A. McAlister,
Justin Ezekowitz,
Nicola Hooton
et al.

Abstract: EART FAILURE IS THE FASTest growing cardiovascular diagnosis in the United States, with a community prevalence of 2.5% in adults, and the direct and indirect costs of heart failure exceed $33 billion per year. 1 Despite many advances in diagnosis and pharmacotherapy for heart failure during the past 2 decades, morbidity and mortality remain high and quality of life is poor for many patients. Thus, there is increasing enthusiasm for the therapeutic potential of atrial-synchronized biventricular pacemakers (card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
359
3
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 552 publications
(377 citation statements)
references
References 139 publications
8
359
3
7
Order By: Relevance
“…The proposed mechanism includes both improved pump efficiency and reversal of deleterious myocardial remodeling. Results from mechanistic studies, observational evaluations, randomized controlled trials and their meta-analyses have consistently demonstrated significant improvement in quality of life, functional status, exercise capacity, hospitalization, and mortality in patients with New York Heart Association (NYHA) class III and IV HF and electrical dyssynchrony who are randomized CRT [7]. More recently the MADIT-CRT trial demonstrated improvement in all cause mortality and progression of heart failure in patients with NYHA class I and II, prompting expansion of CRT indications to include all patients with heart failure with impaired systolic function and left bundle branch block morphology on EKG [8].…”
Section: Discussionmentioning
confidence: 99%
“…The proposed mechanism includes both improved pump efficiency and reversal of deleterious myocardial remodeling. Results from mechanistic studies, observational evaluations, randomized controlled trials and their meta-analyses have consistently demonstrated significant improvement in quality of life, functional status, exercise capacity, hospitalization, and mortality in patients with New York Heart Association (NYHA) class III and IV HF and electrical dyssynchrony who are randomized CRT [7]. More recently the MADIT-CRT trial demonstrated improvement in all cause mortality and progression of heart failure in patients with NYHA class I and II, prompting expansion of CRT indications to include all patients with heart failure with impaired systolic function and left bundle branch block morphology on EKG [8].…”
Section: Discussionmentioning
confidence: 99%
“…Las características generales de nuestros pacientes son comparables a las series internacionales 12 , aunque existen algunas diferencias importantes. Así por ejemplo, los estudios con distribución aleatoria han excluido sistemática-mente a pacientes en FA, que en nuestra serie correspondían a 1 de cada 5 sujetos.…”
Section: Discussionunclassified
“…20) The clinical applications of the pacing method known as CRT alone (CRT-P) began by using an epicardial lead in 1994. 21) Recent meta-analysis 11,22,23) demonstrated that CRT-P improved LVEF, QOL, and functional status, and reduced hospitalization for heart failure and mortality from all causes. However, it has not been determined whether CRT-P has a potential to suppress lethal arrhythmia or sudden cardiac death 22) (Figure 2).…”
Section: Dysfunction (Lvef 35%)mentioning
confidence: 99%
“…The implantation of ICD, CRT-D and CRT-P are useful for improving the prognosis and/or sudden cardiac death event rate in patients with heart failure and/or fatal ventricular arrhythmias (ventricular tachycardia: VT/ventricular fibrillation: VF). [4][5][6][7][8][9][10][11] This review paper was written mainly to identify the indications for ICD/CRT-P or CRT-D on the basis of the 2006 JCS guidelines. 3) Further, the usefulness of pharmacological tests for the choice of effective drugs to treat lethal arrhythmia and electrophysiological tests for prognosis, especially in patients with dilated cardiomyopathy, have been questioned recently.…”
Section: Introductionmentioning
confidence: 99%